Data security and storage in cloud using hybrid algorithms - Archana, L; P. K. Devan, K; Harikumar, P (International Journal of Engineering and Technology, 2018)
Cloud Computing has already grabbed its roots in many industries. It has become a fascinating choice for small budget organizations, as On-demand resources are available on pay as you use basis. However, security of data being stored at cloud servers is still a big question for organizations in today’s digital era where information is money. Large organizations are reluctant to switch to cloud services since they have threat of their data being manipulated. Cloud service provider’s claim of providing robust security mechanism being maintained by third party, but still there are many reported incidents of security breach in cloud environment in past few years. Thus, there is need for ro-bust security mechanism to be adopted by cloud service providers in order for excelling cloud computing. Since there are n number of data’s in cloud, Storage of those data are to be placed with high rank of Significance. In Existing system, no efficient hybrid algorithms are used there by security and storage is compromised to significant ratio. We propose AES and Fully Homomorphic algorithm to encrypt the data, thereby file size get is compressed thereby increasing Data security and stack pile.